2017
DOI: 10.4149/neo_2017_110
|View full text |Cite
|
Sign up to set email alerts
|

miR-33a expression sensitizes Lgr5+ HCC-CSCs to doxorubicin via ABCA1

Abstract: Cancer stem cells (CSCs) are responsible for the unrestrained cell growth and chemo-resistance of malignant tumors. Reports about miR-33a in different type of cancer are limited, and it remains elusive whether there is a link between miR-33a and chemo-resistance of CSCs. Here we report that Lgr5+ hepatocellular carcinoma (HCC) cells from primary tissues and cell lines behave similarly to CSCs and are chemo-resistant to doxorubicin. Significantly, reduced miR-33a expression is associated with the chemo-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…This implies that low SLC27A2 expression level induces ABCG2 expression by down-regulating miR-411. The ABC transporter family has at least 48 members identified in humans, and 12 of these are recognized putative drug transporters [13][14][15]. When tumor patients have higher expression of ABC transporter pumps, they usually do not respond to chemotherapy because the ABC transporters located on the cytoplasm side of the resistant cell effluxes chemotherapeutic drugs out of the tumor cells, thus leading to chemo-resistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that low SLC27A2 expression level induces ABCG2 expression by down-regulating miR-411. The ABC transporter family has at least 48 members identified in humans, and 12 of these are recognized putative drug transporters [13][14][15]. When tumor patients have higher expression of ABC transporter pumps, they usually do not respond to chemotherapy because the ABC transporters located on the cytoplasm side of the resistant cell effluxes chemotherapeutic drugs out of the tumor cells, thus leading to chemo-resistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…The leucine-rich, repeat-containing, G protein-coupled receptor 5 (LGR5), another marker of cell plasticity and stem cell potential in LC, is expressed only in HuH7- and HuH6-EVs. It has been suggested that LGR5-expressing HCC stem-like cells may play an important role for the pathogenesis and drug resistance of HCC [ 39 ]. It is possible that EpCAM-, E-cadherin- and LGR5-carrying EVs participate to the preparation of the microenvironment to accommodate the subpopulation of tumor stem like cells originating from the LCC.…”
Section: Discussionmentioning
confidence: 99%
“…1F). Similarly, Hou et al (37) have reported that miR-33a overexpression in Lgr5+ hepatoma-cancer stem cells decreases ATP-binding cassette transporter A1 (ABCA1) expression, thereby reducing the resistance of these cells to doxorubicin (Fig. 1G).…”
Section: Mir-33a and Its Role In Cancermentioning
confidence: 73%